If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + (2d + -3) = 13(d + -1) Reorder the terms: d + (-3 + 2d) = 13(d + -1) Remove parenthesis around (-3 + 2d) d + -3 + 2d = 13(d + -1) Reorder the terms: -3 + d + 2d = 13(d + -1) Combine like terms: d + 2d = 3d -3 + 3d = 13(d + -1) Reorder the terms: -3 + 3d = 13(-1 + d) -3 + 3d = (-1 * 13 + d * 13) -3 + 3d = (-13 + 13d) Solving -3 + 3d = -13 + 13d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-13d' to each side of the equation. -3 + 3d + -13d = -13 + 13d + -13d Combine like terms: 3d + -13d = -10d -3 + -10d = -13 + 13d + -13d Combine like terms: 13d + -13d = 0 -3 + -10d = -13 + 0 -3 + -10d = -13 Add '3' to each side of the equation. -3 + 3 + -10d = -13 + 3 Combine like terms: -3 + 3 = 0 0 + -10d = -13 + 3 -10d = -13 + 3 Combine like terms: -13 + 3 = -10 -10d = -10 Divide each side by '-10'. d = 1 Simplifying d = 1
| A=1/2(10+7)4 | | 4.9q-5.1-5.3q=-1.4q-4.8 | | -45m+68=84m | | 9x+6=7+18 | | 6x+5x+4+9=8x+4+2x | | 3n+2(n+4)=56 | | 111=79 | | 5.7q-1.3-5.6q=0.9q-3.4 | | -54-8v=-7v+21 | | x^2-2x=-5 | | -x+5=-8x+6 | | -4x-2(-5x-1)=-6.5+2(10-x) | | 4-(5-7x)=2(x+1) | | M-27=-46 | | (2a+3b+4c)+(4a+2b)= | | 2u=10 | | 7=t+6 | | 7 = t + 6 | | X(x-4)(x+7)(2x-9)=0 | | 9x=-8y+72 | | 3(7+x)=24 | | 7x+5=21 | | 3x^3-24x^2+36x=0 | | 11k-8k-3=9 | | -x+7=8 | | (2x+3)(x-5)=2(x^2-6x+5) | | 3t+8(2t-6)+2=14t | | Y^2+2y-120=0 | | y=2.6 | | 7k-8-2(k-12)=52 | | 10+x^2-7x=0 | | a^2=24-10a |